FUNGSI PEMERINTAH DALAM PELAYANAN PUBLIK (Kasus Pengujian Kendaraan Bermotor Pada Uptd Dinas Perhubungan Informasi Dan Komunikasidi Kabupaten Kampar) - Suprianto "; Hery Suryadi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
In Kampar government functions in terms of the implementation of the public service in motor vehicle feasibility test basically already done, just that in the implementation of these things – there are still things that are considered incompatible with the standard operational procedure. According to Perda Kampar in 2010 of the standard public service (SPP) and standard Operasioanal (SOP) Service UNIT for the testing of motor vehicles and the establishment and organization of the Department of arrangement of Kampar, motor vehicle testing unit established within one agency Implementing Technical Service Unit (UNIT) Testing of motor vehicles under the Department of transportation, communication and Informatics of Kampar Regency. UNIT Testing a motor vehicle (PKB) Kampar Regency, periodically testing the feasibility of public motor vehicles in Kampar.on the practice test implementation feasibility dilapangannya motorists who do UNIT Testing of motor vehicles (PKB) Kampar it was still prone to going wild (pungli) levy. A number of citizens claiming to be concerned with an action that is usually pungli often occur. Phenomenon that occurs when the real testing of motor vehicles made there is often a pungli. Pungli done ostensibly for easier management.Weak control of the Government with respect to the performance of an employee as well as the lack of a sense of responsibility to the safety of passengers on public transport, making the employees unable to provide public services.The results of this study the author gives the conclusion that the function of the Government in the public service in motor vehicle feasibility test cases covering fairness, simplicity, compassion, reliability, comfort, and trust is good enough. This is demonstrated by the responses of the respondents who are likely to declare less well, however by the presence of a pretty good response from respondents does not mean existing in the service UNIT for information and communication Department of transportation district of Kampar is already very good, but there is still need for improvement of quality of service to the community is really satisfied with the service given by the employees of theUNIT for information and communication Department of transportation district of Kampar.Keywords: Government, Public Service Function, Test Eligibility